Control of vascular tone via transformation of hydrogen peroxide - Stocker, Roland (Henry Stewart Talks, 2023)
Arterial relaxation, Indoleamine 2,3-dioxygenase (IDO) and L-tryptophan metabolism, IDO1 and blood pressure in systemic inflammation, Mechanism of IDO1-mediated arterial relaxation and blood pressure lowering, Redox signaling by cis-WOOH, cis-WOOH and PKG1α oxidation